Modifiable Risk Factors for Developing Diabetes Among Women With Previous Gestational Diabetes - Bao-Ping Zhu, MD, MS; Nisreen H. Kabeer, MPH; Shumei Yun, MD, PhD; Ross C. Brownson, PhD (Centers for Disease Control and Prevention, 2007)
IntroductionGestational diabetes mellitus (GDM) affects approximately 2% to 4% of all pregnant women in the United States each year. Women who have had GDM are at high risk for developing nongestational diabetes. The objective of this study was to assess the prevalence of modifiable risk factors for developing diabetes among women with previous GDM only.MethodsCross-sectional data for nonpregnant women from the 2003 Behavioral Risk Factor Surveillance System were used to estimate and compare the prevalence of modifiable risk factors among three groups: nonpregnant women with previous GDM only, nonpregnant women with current diabetes, and nonpregnant women without diabetes.ResultsIn 2003, 7.6% of nonpregnant women aged 18 years and older in the United States had current self-reported physician-diagnosed diabetes, and 1.5% had previous GDM only. Compared with women without diabetes, women with previous GDM only had higher prevalence of no leisure-time physical activity (32.0% vs 25.7%), overweight (62.2% vs 49.0%), and obesity (29.4% vs 20.0%). After adjusting for sociodemographic variables, women with previous GDM only were more likely to have no leisure-time physical activity (prevalence odds ratio [POR], 1.4; 95% confidence interval [CI], 1.2-1.7) and more likely to be overweight (POR, 1.8; 95% CI, 1.6-2.2) or obese (POR, 1.7; 95% CI, 1.4-2.1), compared with women with no diabetes. ConclusionWomen with previous GDM are more likely to have modifiable risk factors for developing diabetes than women without diabetes. More attention to this issue is needed from health care providers and public health officials to encourage the promotion of healthy lifestyles during and after pregnancy.